La grafología forense como prueba pericial en el reconocimiento de la falsificación de firmas (2014)
In this paper we will demonstrate the importance of the criminal investigation and the various advances in forensic graphology has had since its inception to the present day, the criminal investigation should be understood as the joint work developed by expert personnel as through the different stages that occur can reach a conclusion In the particular case, the criminal news broke due to the complaint I make Mr. Miguel Antonio Caro to prosecutors against Juan Manuel Jurado Rico for fraud, as this ensures that Mr. Juan Manuel Jurado Rico, falsify his signature on 10 checks worth $ 300 million The importance of Case International Bussines Caro, which often lies in Colombia, this type of crime occurs; For the case study, discipline used was forensic graphology, the prosecutor ask the lab graphology and forensic documentología DIJIN, making the scriptural samples involved in the case, once it is filled out the consent Act (FPJ-28) proceeded to the taking of samples by the expert, asking the clerks to undertake various writings, where different aspects were studied: tilt, pressure, pace firmness, speed and flow. Through the opinion given by the expert is able to establish which of the persons involved, (Dora Luz Diaz Martinez and Juan Manuel Jurado Rico) was the one that forged the signature of Mr. Miguel Antonio Caro